Effect of Polymerization Temperatures on Polyaniline Coated Fiber Bragg Grating Sensor for Chloroform Detection. Issue 1 (19th December 2018) - Ahad, Irma Z. M.; Harun, Sulaiman W.; Gan, Seng Neon; Phang, Sook Wai
Abstract : A new fiber Bragg grating (FBG) sensor based on polyaniline (PAni) has been developed for chloroform detection. PAni was synthesized through chemical oxidation method by using equimolar amount of aniline monomer (Ani), dioctyl sodium sulfosuccinate dopant (AOT) at different three polymerization temperatures (−5, 0 and 25 °C). The chemical structure and conducting behavior of PAni were confirmed using Fourier transform infrared (FTIR) spectroscopy, ultraviolet‐visible (UV‐vis) spectroscopy and conductivity measurements. In this study, the FBG sensor was produced by removing the cladding layer and replaced with PAni coating. The immersion of sensor in varying concentration of chloroform (from 10 to 100 ppm) produced different Bragg wavelength shift at ∼1557 nm in the optical spectrum analyzer (OSA). The effect of PAni polymerized at different polymerization temperatures affect the sensor performance. It was found that the FBG sensor coated with PAni polymerized at 0 °C exhibited the highest sensitivity for chloroform detection and good recyclability up to 10 cycles with fast response time of 7 s and recovery time of 8 s. The FTIR, UV‐vis and conductivity analyses supported the proposed mechanism for the interaction between PAni and chloroform being the dipole‐dipole interaction (physical interaction) between the partial negative charge (Cl δ− ) of chloroform and the partial positive charge (NH δ+ ) of PAni.